2020
DOI: 10.1021/acs.joc.0c00471
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Phosphine Ligand-Enabled Gold(I)-Catalyzed O-Nucleophilic Addition of N-Hydroxybenzo[1,2,3]-triazin-4(3H)-ones to Alkynes Followed by [3,3]-Rearrangement: Simultaneous Formation of C–O and C–N Bonds

Abstract: We describe a gold (I)-catalyzed tandem O-nucleophilic addition/[3,3]-rearrangement reaction of N-hydroxybenzo­[1,2,3]-triazin-4­(3H)-ones with alkynes enabled by a biphenyl-2-yl phosphine ligand featuring a pendant amide moiety (L1). A variety of 1-(2-oxo-2-arylethyl)­benzo [d]­[1,2,3]­triazin-4­(1H)-one derivatives were synthesized in good to excellent yields. The present protocol gives a rare example of simultaneous formation of C–O and C–N bonds in the gold­(I)-catalyzed [3,3]-sigmatropic rearrangements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In 2020, Liu's group reported that WangPhos could promote the O-nucleophilic addition of N-hydroxybenzo [1,2,3]-triazin-4(3 H)-ones 2 to alkynes (Scheme 3). 42 The resulting isolable intermediate 3 subsequently underwent a [3+3]-sigmatropic rearrangement to afford 1-…”
Section: Accelerated Addition To Alkynes By Oxygen-based Nucleophilesmentioning
confidence: 99%
“…In 2020, Liu's group reported that WangPhos could promote the O-nucleophilic addition of N-hydroxybenzo [1,2,3]-triazin-4(3 H)-ones 2 to alkynes (Scheme 3). 42 The resulting isolable intermediate 3 subsequently underwent a [3+3]-sigmatropic rearrangement to afford 1-…”
Section: Accelerated Addition To Alkynes By Oxygen-based Nucleophilesmentioning
confidence: 99%
“…Rearrangement reactions of N -arylhydroxylamine derivatives have been rigorously investigated by the Nakamura group for the syntheses of highly functionalized aniline derivatives via Co- and Cu-catalyzed [1,2]- and [1,3]-rearrangements (Scheme a-i). , The Zhao group reported an Ir-catalyzed [3,3]-rearrangement involving N–O bond cleavage of N -phenoxyacetamide (Scheme a-ii) . A few reports of Au- and Zn-catalyzed tandem nucleophilic addition/[3,3]-rearrangement reactions of hydroxybenzotriazole and alkyne derivatives have been documented (Scheme a-iii) . The Hong group reported visible light-induced heterolytic N–O bond cleavage of N -alkoxypyridinium salts via single-electron transfer (SET), leading to remote pyridyl functionalizations (Scheme a-iv) .…”
mentioning
confidence: 99%